Histopathological changes of the cardiac muscle and the adrenal gland in long term diabetic rat - Abdullah, Sinan Mohammed; Abdul Razak, Tariq; Al-Ani, Imad Matloub Dally (2014)
Diabetes in an animal model is increasingly being used in the investigation of the etiopathogenesis of diabetes and diabetic complications in the long term. Streptozotocin is the chemical used to induce experimental diabetes, mostly in rodents. Administrations of the STZ to adult rats cause insulin-dependent type 1 diabetes. Cardiovascular diseases as a long-term complication may be found in diabetic experimental animals. These complications are the most significant and commence one of the leading causes of mortality due to diabetes. On the other hand, Diabetes mellitus is associated with abnormal function of the adrenal gland. The aims of this study were to investigate the histopathological changes of cardiac muscle and adrenal gland in diabetic rats. Sixteen adult female Sprague–Dawley rats weighing 200–225g at testing were used. All animals were housed in groups of 2-3 in a temperature (22±1 ºc) and relative-humidity (60–70%) controlled room on a 12:12-h light/dark cycle and allowed free access to water and normal diet for rodents. Animal care complied with that stipulated by the local ethics committee. The rats were randomly divided into 2 groups of 8 animals. Streptozotocin was dissolved in 0.1M Citrate Buffer at pH 4.5 immediately before i.p. Injection at 60mg/kg. Eight rats (diabetic group) received a single i.p. Injection of Streptozotocin (60 mg/kg body weight) following an overnight fast. After six months, animals from control and treated groups (STZ) were sacrificed; dissected and small pieces of the heart and adrenal gland were quickly removed, then fixed in 10% formalin. Following fixation, specimens were dehydrated, embedded, and then sectioned to 4 microns thickness. For histological examinations, sections were stained with Ehrlich Haematoxylin and Eosin. In conclusion, the long-term diabetic rat may act as a useful model to observe the histopathological changes of the cardiac muscle and the adrenal gland in long-term diabetic human.